Physicochemical Properties and Biological Activities of Silver Carp Scale Peptide and Its Nanofiltration Fractions - Zu, Xiao-yan; Zhao, Ya-jing; Fu, Shi-ming; Liao, Tao; Li, Hai-lan; Xiong, Guang-quan (Frontiers in Nutrition, 2022)
Silver carp scale peptide (SCSP) obtained by enzymatic hydrolysis and its fractions SCSP-I, II, and III obtained by nanofiltration were assessed. The solubility of each fraction of SCSP was higher than 90%, SCSP-II and III having solubilities higher than 95%. The antioxidant powers on •OH, O2-• and Fe3+ were ranked as SCSP-III > SCSP-II > SCSP-I > SCSP. All fractions of SCSP had no toxic or side effects in mouse B16 melanoma cells experiments in vitro. At a concentration of 0.01 mg/mL, the tyrosinase activity of the SCSP-II fraction was significantly lower than that of the α-arbutin (P<0.05), at 65.37%. The molecular weight distribution of SCSP was 399.83-1404.62 Dalton, and 13 peptide sequences were detected. Among them, SCSP-II contained many hydrophobic amino acids, and SCSP-III stood out for combining arginine with hydrophobic amino acids. This may be the reason why the low molecular-weight SCSPs show the strong antioxidant activity and strong tyrosinase inhibition.